THE IMPACT OF FINANCIAL DEVELOPMENT ON ECONOMIC GROWTH IN A SELECTED SAMPLE OF ESCWA COUNTRIES FOR THE PERIOD (2004-2021) USING (PANEL DATA): FINANCIAL DEVELOPMENT, ECONOMIC GROWTH - Al-Hakari, Nada; Hayawi, Kalthoum (Humanities Journal of University of Zakho, 2024)
This study aimed to measure the impact of the relationship between financial development and economic growth in the countries of ESCWA region using panel data during the time period 2004-2021, on a sample of nine countries from the ESCWA region (Iraq- Saudi Arabia- Egypt- Qatar- Morocco- Jordan- Lebanon- Oman- Kuwait), and for five financial development indicators: Domestic credit provided to the private sector/GDP, Broad Money Supply/GDP, Percentage of Deposits/GDP, Value of Shares Traded/GDP, and Number of Listed Local Companies. . The first three are the indicators of the banking sector and the last two represent indicators of financial markets The Trade Openness Index represented a control indicator model or auxiliary to explanatory indicators and the Average per Capita GDP as an indicator expressing the dependent variable. The study used the descriptive analytical approach as well as the standard quantitative approach forming the model is based on the outputs of (Eviews 12). The model was estimated by using three panel data models: The Pooled Regression Model, The Fixed Effects Model, and the Random Effects Model. The results of statistical tests indicated that the fixed effects model was the best fit. the results of the assessment indicated that there are indicators of the development of the banking sector, represented by Broad Money Supply/GDP and the Ratio of Bank Deposits/GDP, that had a non-significant positive effect on economic growth, while the other indicator, Domestic Credit Ratio Provided to The Private Sector/GDP, had a non-significant negative impact on economic growth in the countries of the ESCWA region during the period 2004-2021. The control indicator in the model, Trade Openness, had a significant negative impact on economic growth in the countries of the ESCWA region during the period 2004-2021.These findings suggest that the financial sector suffer from weakness in the performance of their functions and therefore needs measures to enhance economic growth in these sectors through reform measures in these sectors to to increase their effectiveness. This includes increasing the broad money supply and the percentage of bank deposits and providing an appropriate environment represented through legislation and regulations controlling the performance and development of their relationship.